PENGARUH FAKTOR INTERNAL TERHADAP MINAT BERWIRAUSAHA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS JAMBI - Winda Syafitri; dahmiri dahmiri (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
The purpose of this research is to explain the effect of Internal Factors toward student interest in entrepreneurship on Economics and Business Faculty of Jambi University. Sampling techniques used on is Non-Probability Sampling with Convenience Sampling Method. The number of respondents is 100 consumers. Technique analysis for this research use descriptive analysis to describe the research variables and multiple regression analysis to find the effect between research variables using SPSS 20.0. This research revealed the significant effect of Internal Factors on Student Interest in entrepreneurship on Economics and business Faculty of Jambi University.